A History of Research on the Aramaic Dead Sea Scrolls - Jones, Robert E. (2023)
The Aramaic Dead Sea Scrolls have attracted increasing scholarly attention since their official publication was completed in 2009. These manuscripts, representing about thirty distinct compositions, attest to the existence of a previously unknown Jewish Aramaic scribal culture that flourished in the early Hellenistic period (ca. late fourth to mid-second centuries BCE). The Aramaic Scrolls thus have the potential to illuminate an otherwise poorly understood period of Jewish history. In this article, I discuss the various scholarly approaches to their language, literary content, and social location, with a special emphasis on trends in the secondary literature since the late 2000s. This article will also provide interested students and scholars with an overview of the major themes and concerns found throughout the Aramaic Scrolls.
Keywords: Scribalism; Apocalypse; Priesthood; Hebrew Bible; Hellenistic Period; Ancient Judaism; Dead Sea Scrolls; Qumran; Aramaic